Effects of hypolimnetic oxygenation on fish tissue mercury in reservoirs near the new Almaden Mining District, California, USA. (1st January 2021) - Seelos, Mark; Beutel, Marc; Austin, Carrie M.; Wilkinson, Elisabeth; Leal, Clayton
Abstract: Almaden, Calero, and Guadalupe reservoirs (San Jose, CA, USA) are small (<13 million m 3 ) surface water reservoirs polluted by the former New Almaden Mining District, North America's most productive historical mercury (Hg) mine. Stevens Creek Reservoir (Cupertino, CA, USA) also has elevated fish Hg concentrations, but no historical mining source. We report a 15-year dataset to evaluate the effectiveness of line diffuser hypolimnetic oxygenation systems (HOSs) in reducing methylmercury (MeHg) concentrations in reservoir water and fish after four consecutive years of operation. HOSs were installed in each reservoir to increase dissolved oxygen concentrations in bottom water, thereby suppressing the activity of anaerobic bacteria (e.g., sulfate-reducing bacteria) known to produce MeHg. Before HOS operation, MeHg concentrations increased in bottom waters of all four reservoirs during periods of thermal stratification and profundal hypoxia. MeHg concentrations decreased significantly in bottom waters during HOS operation, with mean reductions of 63%–85% below pre-oxygenation concentrations. However, MeHg concentrations were unchanged or increased in surface waters. This could be the result of enhanced mixing between surface and bottom waters as a result of line diffuser oxygenation, or continued Hg methylation occurring in the oxic water column and littoral sediments. Despite little change in whole water column MeHg concentrations, we observed modest but significant declining trends in fish tissue Hg in Guadalupe and Stevens Creek reservoirs. Results suggest that oxygenation, rather than directly lowering MeHg in water, may have mixed nutrients into surface waters, thereby enhancing primary productivity and indirectly affecting Hg bioaccumulation by diluting concentrations in phytoplankton. Graphical abstract: Image 1 Highlights: Oxygenation systems lowered methylmercury concentrations in bottom water. Phytoplankton productivity increased in surface waters during oxygenation. Fish mercury is declining in two of four oxygenated reservoirs. Abstract : Mercury concentrations in fish are declining in two of four California water reservoirs treated with line-diffuser hypolimnetic oxygenation systems.